Long-Term Exposure of MoS2 to Oxygen and Water Promoted Armchair-to-Zigzag-Directional Line Unzippings - Youngho Song; Minsuk Park; Junmo Park; Hyun S. Ahn; Tae Kyu Kim; Sang-Yong Ju (Nanomaterials, 2022)
Understanding the long-term stability of MoS2 is important for various optoelectronic applications. Herein, we show that the long-term exposure to an oxygen atmosphere for up to a few months results in zigzag (zz)-directional line unzipping of the MoS2 basal plane. In contrast to exposure to dry or humid N2 atmospheres, dry O2 treatment promotes the initial formation of line defects, mainly along the armchair (ac) direction, and humid O2 treatment further promotes ac line unzipping near edges. Further incubation of MoS2 for a few months in an O2 atmosphere results in massive zz-directional line unzipping. The photoluminescence and the strain-doping plot based on two prominent bands in the Raman spectrum show that, in contrast to dry-N2-treated MoS2, the O2-treated MoS2 primarily exhibits hole doping, whereas humid-O2-treated MoS2 mainly exists in a neutral charge state with tension. This study provides a guideline for MoS2 preservation and a further method for generating controlled defects.